Pengaruh Waktu Pemeraman Dengan Penambahan Kapur Sebagai Bahan Additve Pada Tanah Lempung Ekspansif Terhadap Nilai CBR Tanah - Bahtiar Efendi Situmorang; Melloukey Ardan (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2019)
The soil is an essential element of a structure under construction so that the soil should have a good carrying capacity. But the fact the field is found soil that has the low bearing capacity, so it is necessary to conduct soil stabilisation with lime. The study aims to determine the percentage that is effective in adding lime and the effect of adding lime to the soil physical properties change in terms of the value of CBR (California Bearing Ratio) to the long curing time. This research was conducted in the laboratory, by testing the physical properties of soil and the strong support of land (CBR) with the addition of lime variation of 1%, 3%, and 5% by long curing 0, 4, 7 and 14 days. Tests were conducted with two treatments, soil samples were cured first and then compacted and samples were pressed first and brooded. The result is the value of CBR. %. From the results of the value of the California Bearing Ratio can be seen that the addition of sand quarsa on soil clays showed an increase in the value of the California Bearing Ratio in soil clays.